FAKTOR LINGKUNGAN YANG BERKORELASI DENGAN KUALITAS TIDUR PASIEN KRITIS DI RUANG PERAWATAN INTENSIF (INTENSIVE CARE UNIT/ICU) - Erlangga Galih Zulva Nugroho; Heryanto Adi Nugroho; Abdurrahman Abdurrahman; T. Iskandar Faisal; Afdhal Afdhal; Nana Rochana (Jurnal Ilmu Keperawatan Medikal Bedah, 2022)
Rest and sleep are basic requirements needed by all people. Everyone needs a good quality of rest and sleep to be able to repair or restore the body and maintain the health, including critically ill patients in Intensive Care Unit. Rest and sleep are influenced by several factors such as the disease process, environmental, psychological stress, and medications. However environmental factors are factors that can be modified directly in order to meet this requirement. The purpose of this study is to determine the relationship between environmental factors and the quality of sleep in critically ill patients in the Intensive Care Unit of Semarang. This type of research was quantitative descriptive with correlational design. The data collection method was cross sectional. The samples in this study included 60 people. The results showed that the mean of environmental factors and sleep quality were 88,28 ± 29,76 dan 13,50 ± 4,9 respectively.There was a relationship between environmental factors and the quality of sleep critically ill patients in the ICU with p-value 0.009 (p-value <0.05). The better the environmental factors that are in the ICU the better the sleep quality of critical patients. It is suggested that the hospitals could manage the most disturbing noise caused by other patients to improve the quality of these critically ill patients.